Developing and validating a scale to measure the perceptions of safety, usability and acceptability of microarray patches for vaccination: a study protocol - Matthew N. Berger; Cristyn Davies; Erin Mathieu; Ramon Z. Shaban; Shopna Bag; S. Rachel Skinner (SAGE Publishing, 2024)
Background: Vaccination is a fundamental tenet of public and population health. Several barriers to vaccine uptake exist, exacerbated post-COVID-19, including misconceptions about vaccine efficacy and safety, vaccine hesitancy, vaccine inequity, costs, religious beliefs, and insufficient education and guidance for healthcare professionals. Vaccine uptake may be aided using microarray patches (MAPs) due to reduced pain, no hypodermic needle, enhanced thermostability, and potential for self and lay administration. Objectives: This protocol outlines the development of a scale that aims to accurately measure the perceived safety, usability, and acceptability of MAPs for vaccination among laypeople, MAP recipients, clinicians, and parents or guardians of children. Methods and analysis: This study will follow three phases of scale development and validation, including (1) item development, (2) scale development, and (3) scale evaluation. Inductive (interviews) and deductive methods (literature searches) will be used to develop scale items, which experts from target populations will assess through an online survey. Cognitive interviews will be conducted to observe their processes of answering the draft survey. Thematic analysis will be conducted to analyse qualitative data. Lastly, four surveys will be administered online to our target populations over two time points to determine their repeatability. Exploratory and confirmatory factor analyses, Cronbach's alpha, and construct validity will be performed. Ethics: This study was approved by Metro South Health (HREC/2021/QMS/81653) and Western Sydney Local Health District (2023/ETH00705) Human Research Ethics Committees. Discussion: The scale will support a standardised approach to assessing the social and behavioural aspects of MAP vaccines, enabling comparison of outcomes across studies. Once validated, this scale will assist vaccination programmes in developing effective strategies for integrating MAPs and overcoming barriers to vaccination. This includes improving vaccine equity and accessibility, especially in lower- and middle-income countries and rural or remote locations.